Detección de incidencias y fallos en redes de comunicaciones utilizando herramientas de libre acceso - Quintero Arias , Dany Mishel (2024)
The current curriculum integration project focuses on implementing a centralized network monitoring system at Universidad Técnica Estatal de Quevedo (UTEQ), utilizing Zabbix as the primary tool. Exhaustive comparisons were made with other tools such as Nagios and Cacti, with Zabbix standing out for its comprehensive monitoring capability and scalability in enterprise environments. Result verification revealed high system effectiveness, with a 99% accuracy in event detection and notification, and an average response time of 0.553 seconds. This detailed analysis provided a comprehensive view of the system's performance, demonstrating its ability to timely detect and notify critical events, significantly contributing to the security and stability of UTEQ's IT infrastructure. Additionally, a satisfaction survey conducted with the head of the TICS department reflected a notable increase in satisfaction levels, showing substantial improvements in operational efficiency and IT resource management after Zabbix implementation. Before adopting Zabbix, the administrator faced significant challenges in effective network monitoring, impacting operational efficiency. However, with Zabbix implementation, a substantial improvement was observed in monitoring capability, incident detection, and overall IT infrastructure management, resulting in notable process optimization and a tangible improvement in administrator satisfaction. This transition to Zabbix has enabled more efficient and proactive network management, ensuring operational continuity and communication system security at UTEQ